2019
DOI: 10.1161/jaha.118.010881
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of Patients With Malignancy and Takotsubo Syndrome: Observations From the International Takotsubo Registry

Abstract: BackgroundClinical characteristics and outcomes of takotsubo syndrome (TTS) patients with malignancy have not been fully elucidated. This study sought to explore differences in clinical characteristics and to investigate short‐ and long‐term outcomes in TTS patients with or without malignancy.Methods and Results TTS patients were enrolled from the International Takotsubo Registry. The TTS cohort was divided into patients with and without malignancy to investigate differences in clinical characteristics and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 24 publications
1
82
1
2
Order By: Relevance
“…They show that TTS in association with A/Ca more often presents as secondary TTS,with associate clinical impact includingsignificantly increased in-hospital MACE rates [17]. Indeed, Cammann et al [8] have recently reported, within the InterTAK cohort, increased in-hospital death rates in patients with A/Ca and TTS. They also show that patients with A/Ca have greater risks not only of late all-cause mortality, but (2) and (3) point strongly to some substantial and ongoing interaction between the presence of cancer and the probability of CVS complications (shortand long-term) of TTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They show that TTS in association with A/Ca more often presents as secondary TTS,with associate clinical impact includingsignificantly increased in-hospital MACE rates [17]. Indeed, Cammann et al [8] have recently reported, within the InterTAK cohort, increased in-hospital death rates in patients with A/Ca and TTS. They also show that patients with A/Ca have greater risks not only of late all-cause mortality, but (2) and (3) point strongly to some substantial and ongoing interaction between the presence of cancer and the probability of CVS complications (shortand long-term) of TTS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, reports have been made from several groups, including the International InterTAK collaboration, that TTS is often associated with presence of internal malignancy at the time of presentation [8][9][10]. Furthermore, there is a suggestion that TTS represents a basis for increased risk of later emergence of malignancies and for fatal outcomes from those malignancies [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…12 One of the hypothesis is that cancer and TTS share similar triggering mechanisms, which consist in activation of the sympathetic nervous system. 8,13 Therefore, TTS patients with cancer should be considered a high-risk subgroup with respect to their increased mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although most patients with TTS experience complete cardiac function recovery, the risk of complications is similar to that in patients with acute coronary syndrome. 13 Patients who survive an acute episode typically recover systolic function within one to four weeks. 1,3 Our patient recovered the systolic function within two weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the multicenter GEIST (German Italian Stress Cardiomyopathy) Registry data failed to identify any independent predictors of TTS recurrence [28]. Presence of malignancy has been shown to be associated with higher risk of TTS in numerous studies [29][30][31], and there are numerous reports of TTS associated with chemotherapy or immunotherapy [32][33][34][35][36]. It is plausible that interruption in chemotherapy after initial episode of TTS may play a role in explaining the lack of difference in TTS recurrence rate in those with malignancy.…”
Section: Discussionmentioning
confidence: 99%